FAILURE ANALYSIS OF POLYVINYLIDENE FLUORIDE BY DEGRADATION FOR A PIPELINE - RAZAK, ARIFF QAMARUDDIN (IRC, 2020)
This present paper describes how polyvinylidene fluoride combats corrosion issue in pipeline of oil and gas industry. This study is crucial due to limited studies have been made upon polyvinylidene fluoride as a material for pipeline to prove its reliability and sustainability in the industry. Polyvinylidene fluoride will be tested upon its degradation over time. Tests will be executed upon the specimens of this material to prove that polyvinylidene fluoride has the better properties and favor compared to conventional materials in pipeline which are stainless and carbon steel. Upon this, the specimens of polyvinylidene fluoride will undergo tests to observe its water and chemical absorption at various parameters. Every samples of polyvinylidene fluoride will be tested upon its weight. This will show whether polyvinylidene fluoride is reliable due to its absorption rate. Study of this material will beneficial to oil and gas industry in future upon the reliability of polymers to sustain in oil and gas industry.